Presentation and effectiveness of early treatment of type 2 diabetes in youth: lessons from the TODAY study. Issue 3 (17th February 2015) - Kelsey, Megan M; Geffner, Mitchell E; Guandalini, Cynthia; Pyle, Laura; Tamborlane, William V; Zeitler, Philip S; White, Neil H; ,
Abstract : Objective: The objectives were to (i) describe the characteristics of a large ethnically/racially and geographically diverse population of adolescents with recent‐onset type 2 diabetes (T2D), and (ii) assess the effects of short‐term diabetes education and treatment with metformin on clinical and biochemical parameters in this cohort. Research design and methods: Descriptive characteristics were determined for subjects screened for Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) who met criteria for diagnosis of T2D (n = 1092). Changes in clinical and biochemical parameters were determined for those who completed at least 8 wk of the run‐in phase of the trial, which included standardized diabetes education and treatment with metformin. Further analysis determined whether these changes differed according to the treatment at screening. Main outcome measures: Demographic, biochemical measurements, and anthropometrics at screening and changes over 8 wk of run‐in were the outcome measures. Results: Subjects screened for TODAY had a median age of 14 yr and median hemoglobin A1c (HbA1c) of 6.9% (52 mM/M), 2/3 were female, and ethnic/racial minorities were overrepresented. Dyslipidemia and hypertension were common comorbidities. During run‐in, HbA1c, body mass index, low‐density lipoprotein cholesterol, triglycerides, and blood pressure significantly improved. Nearly all participants on insulin therapy at screening were able to attain target HbA1c following insulin discontinuation. Conclusions: Treatment with metformin and diabetes education provided short‐term improvements in glycemic control and cardiometabolic risk factors in a large adolescent T2D cohort. Nearly all insulin‐treated youth could be successfully weaned off insulin with continued improvement in glycemic control.